Reading Related Activities in English Textbook and How the Texts are Exploited in the Classroom - Dewantara, Kadek Andre Karisma; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Journal of Education Reseach and Evaluation, 2022)
Reading comprehension skill is an important requirement that must be possessed by students in learning English. To support students’ reading skill development, the role of the teacher and the learning materials are crucial. This study is an attempt to describe the reading related activities in English text book for Grade 9 and how the texts are exploited in the classroom by teacher. This study uses a descriptive qualitative which analyze the textbook used by the students and observe an English teacher who teach the ninth grade. The data of this research collected through document analysis, classroom observation, and interviews. The data were   analyzed through four processes of data analysis which involved data collection, data reduction, data display and conclusion. The study found that, there are five types of reading related activities contain in English textbook namely: skimming/scanning activities, lexical items activity, linking words activity, activating activity, and questioning activity. Besides that, the most frequent exploited text done by the teacher in the class are completing activity in the form of fill the blank, grammatical words activity, and identifying order of event activity. This research was limited in time, number of subjects and data source so further research is suggested for more generable findings.